2018
DOI: 10.3389/fmicb.2018.00801
|View full text |Cite
|
Sign up to set email alerts
|

De Novo DNA Synthesis in Aedes aegypti Midgut Cells as a Complementary Strategy to Limit Dengue Viral Replication

Abstract: Aedes aegypti is the main vector of Dengue Virus, carrying the virus during the whole mosquito life post-infection. Few mosquito fitness costs have been associated to the virus infection, thereby allowing for a swift dissemination. In order to diminish the mosquito population, public health agency use persistent chemicals with environmental impact for disease control. Most countries barely use biological controls, if at all. With the purpose of developing novel Dengue control strategies, a detailed understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 62 publications
1
28
0
Order By: Relevance
“…The mechanisms behind immune priming induced from the larval stage have not been ascertained yet. Nevertheless, we have recently observed that DNA synthesis and endoreplication participates in the immune priming of adult mosquitoes against DENV and Plasmodium 6,7 . Immune priming in the Anopheles albimanus LSB-AA695BB cell line induced DNA synthesis, increasing the number of TEP and PPO1 gene-copies 7 .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms behind immune priming induced from the larval stage have not been ascertained yet. Nevertheless, we have recently observed that DNA synthesis and endoreplication participates in the immune priming of adult mosquitoes against DENV and Plasmodium 6,7 . Immune priming in the Anopheles albimanus LSB-AA695BB cell line induced DNA synthesis, increasing the number of TEP and PPO1 gene-copies 7 .…”
Section: Discussionmentioning
confidence: 99%
“…albimanus and Aedes aegypti mosquitoes. This indicates that DNA synthesis and endoreplication are part of the mechanisms of memory ( 24 , 25 ). Cisplatin treatment causes the same outcome in monocytes and mosquito cell lines, reducing the expression of the immune response genes related to innate immune memory.…”
Section: Discussionmentioning
confidence: 99%
“…The same occurs in the case of Aedes aegypti infected with dengue virus. When DNA synthesis is blocked by cisplatin, dengue virus is able to replicate in the mosquito midgut ( 24 , 25 ). Hence, midgut cells apparently require the amplification of certain genes, such as TEP1 or PPO1 (but not CTL s), for a fast and effective immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This recently reported phenomenon (Serrato-Salas et al, 2018b), involves increases in de novo DNA synthesis in the midguts of Aedes mosquitoes challenged with inactive DENV-2 particles as well as increased activation of the hindsight and Delta-Notch orthologues. These pathways confer a defence against biotic challenges to mosquitoes by allowing them to rapidly renew tissue in the midgut and thus limit pathogen proliferation (Serrato-Salas et al, 2018a). Insects previously exposed to inactive virus particles seemingly mounted a higher anti-viral response and subsequently the level of DENV infection was greatly reduced compared to naive mosquitoes.…”
Section: Mosquito Defence Against Flavivirusesmentioning
confidence: 99%